2016
DOI: 10.4103/1658-354x.177333
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of oral midazolam and oral dexmedetomidine as premedication in pediatric anesthesia

Abstract: Context:Oral premedication is widely used in pediatric anesthesia to provide preoperative anxiolysis and ensure smooth induction. Midazolam is currently the most commonly used premedicant, but newer drugs such as the α2-agonists have emerged as alternatives for premedication in children.Aims:The aim of this study was to compare clinical effects of oral midazolam and oral dexmedetomidine on preanesthetic sedation and postoperative recovery profile in children.Settings and Design:Randomized controlled trial.Mate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

3
37
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 26 publications
(40 citation statements)
references
References 19 publications
3
37
0
Order By: Relevance
“…Sheta et al reported that incidence of agitation after the administration of 1 μg/kg intranasal dexmedetomidine as premedication was lower than that obtained after 0.2 mg/kg intranasal midazolam in children undergoing full-mouth dental rehabilitation [21]. Jannu et al compared the effect of administering 4 μg/kg of oral dexmedetomidine as premedication with that of administering 0.75 mg/kg of oral midazolam and observed a low incidence of agitation in children premedicated with dexmedetomidine [22]. Jannu preoperative oral administration of 4 μg/kg dexmedetomidine or oral administration of 0.75 mg/kg midazolam decreases the incidence of agitation in children aged 1-7 years [23].…”
Section: Discussionmentioning
confidence: 99%
“…Sheta et al reported that incidence of agitation after the administration of 1 μg/kg intranasal dexmedetomidine as premedication was lower than that obtained after 0.2 mg/kg intranasal midazolam in children undergoing full-mouth dental rehabilitation [21]. Jannu et al compared the effect of administering 4 μg/kg of oral dexmedetomidine as premedication with that of administering 0.75 mg/kg of oral midazolam and observed a low incidence of agitation in children premedicated with dexmedetomidine [22]. Jannu preoperative oral administration of 4 μg/kg dexmedetomidine or oral administration of 0.75 mg/kg midazolam decreases the incidence of agitation in children aged 1-7 years [23].…”
Section: Discussionmentioning
confidence: 99%
“…1,4 Because of its amnestic and anxiolytic properties, midazolam, a GABA A agonist, is the drug most frequently used for paediatric premedication. 5,6 Dexmedetomidine is a highly selective a-2 adrenergic agonist with both sedative and analgesic effects via actions in the CNS. 5,6 Ketamine is an N-methyl-d-aspartate (NMDA) receptor antagonist that produces a state of sedation, anaesthesia, immobility, analgesia, and amnesia.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…5,6 Dexmedetomidine is a highly selective a-2 adrenergic agonist with both sedative and analgesic effects via actions in the CNS. 5,6 Ketamine is an N-methyl-d-aspartate (NMDA) receptor antagonist that produces a state of sedation, anaesthesia, immobility, analgesia, and amnesia. 7,8 Sedative premedication in children is commonly administered via the oral, rectal, sublingual, and intranasal routes with varying degrees of patient acceptance.…”
Section: Editor's Key Pointsmentioning
confidence: 99%
“…Sheta et al reported that the administration of 1 μ g/kg of intranasal DEX as premedication resulted in a lower incidence of ED compared to 0.2 mg/kg of intranasal midazolam in children undergoing full-mouth dental rehabilitation [ 18 ]. Jannu et al compared the effect of administering 4 μ g/kg of oral DEX as premedication to 0.75 mg/kg of oral midazolam and they observed a lower incidence of ED in children premedicated with DEX [ 33 ]. In a similar study, Prabhu and Mehandale reported that 4 μ g/kg of oral DEX was superior to oral midazolam when given as premedication in reducing the incidence and severity of ED [ 34 ].…”
Section: Discussionmentioning
confidence: 99%